Selective intracellular inhibition of signalling pathways - new direction in systematic treatment of psoriasis patients - A. L. Bakulev (State Scientific Center of Dermatovenereology and Cosmetology, 2017)
This article presents current data from publications on new direction in systematic treatment of patients with psoriasis with help of "small molecules" that act intracellularly, selectively inhibiting signaling pathways responsible for production of key pro- and anti-inflammatory mediators that play an important role in the pathophysiology of psoriasis. We discuss key issues that refer to immunopathogenesis of psoriasis, targeted influence of "small molecules" on key components of innate and adaptive immune system of patients psoriasis. This article presents results of the studies performed according to the evidence-based medicine approaches, on the efficiency and safety of apremilast - the first and only current selective inhibitor of intracellular phosphodiesterase 4 - for treating medium-severe and severe psoriasis, including patients with problematic localizations of dermatosis (psoriasis of scalp pilar part, palms, soles, nail plates), as well as in the long run. It is shown that continuous apremilast therapy for the term of 52-156 weeks was accompanied by a significant decrease in prevalence and severity of psoriasis. Adverse events were recorded rarely, they were mild, and frequency of serious adverse reactions was comparable to placebo.